Double-coated lithium-rich manganese-based material, preparation method, application and battery
Doping polyanions in lithium-rich manganese-based materials through sol-gel-ion exchange method and forming a double-covered structure, solving the low efficiency and voltage attenuation of lithium-rich manganese positive electrode materials in the prior art, and achieving efficient lithium ions Battery performance.
Patent Information
- Application Number
- CN202411308415.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-19
AI Technical Summary
In actual applications, the existing lithium-rich manganese positive electrode materials have low initial Coulomb efficiency, poor magnification capacity and severe voltage attenuation, which limits their wide application in lithium-ion batteries.
The double-covered lithium-rich manganese-based material is prepared by sol-gel-ion exchange method. By doping polyanions in the crystal lattice and forming a metal salt coating layer in situ on the surface of the material, a double-covered structure is formed to improve electrochemical performance. .
It achieves high initial capacity, excellent cycling stability and high magnification electrochemical performance, small particles, uniform doping elements, simple preparation method and low cost.
Smart Images

Figure CN119170769A_ABST
Abstract
Description
Technical Field
[0001] The present invention specifically relates to a double-coated lithium-rich manganese-based material, a preparation method, an application and a battery. Background Art
[0002] With the increasing demand for energy in modern society and the rapid development of the electric vehicle market, high-energy-density lithium-ion batteries have received increasing attention among researchers. In current lithium-ion battery systems, there is a capacity mismatch between the positive and negative electrode materials, with the positive electrode capacity being almost an order of magnitude smaller than the anode capacity, which has seriously hindered the development of lithium-ion batteries. Among the many lithium-ion battery positive electrode materials, lithium-manganese-rich based positive electrode materials with the chemical formula xLi2MnO3·(1-x)LiTMO2 (TM=Ni, Mn, Co, etc.) are considered to be one of the most promising candidates due to their outstanding specific capacity. Specifically, the lithium-manganese-rich positive electrode material has a high specific capacity when a Li + The theoretical capacity can reach 250mAh g -1 Above, if completely removed 1.2Li + , the theoretical capacity can reach about 378mAh g -1 In addition, lithium-rich manganese cathode materials have the advantages of low cost, environmental protection and high thermal stability due to their low Co content. Based on these advantages, lithium-rich manganese cathode materials have attracted much attention and have developed rapidly in recent years. Currently, many companies can provide kilogram-level lithium-rich manganese cathode materials.
[0003] However, although lithium-rich manganese cathode materials have outstanding advantages, there are still some unresolved problems, such as low initial Coulombic efficiency, poor rate capacity, and severe voltage decay, which restrict their further practical application. At present, researchers have prepared lithium-rich manganese cathode materials through high-temperature solid-phase synthesis, sol-gel method, and molten salt method, and prepared high-performance lithium-rich manganese cathode materials by controlling synthesis conditions and doping treatment, which have broad application prospects in the field of high energy density lithium-ion batteries.
[0004] Patent document CN114744186A discloses a method for synthesizing a layered lithium-rich manganese-based composite positive electrode material, wherein a sodium salt P2-O3 type composite phase precursor is prepared by sol-gel, and then a lithium salt ion exchange is used to obtain an O6-O3 type composite phase lithium ion battery positive electrode material. Although this patent mentions the preparation of multi-cation-doped lithium-rich manganese materials by sol-gel-ion exchange, it does not involve lithium-rich manganese-based materials modified by polyanion doping, nor does it involve a double coating layer structure. In addition, there are documents showing that the incorporation of polyanions into the lattice can utilize the strong covalent bond between anions and oxygen to reduce the instability of oxygen, thereby reducing the oxygen loss that may occur at high voltage (Huang, Y. et al. Integrated rocksalt-polyanion cathodes with excess lithium and stabilized cycling. Nat Energy (2024).), but this document not only does not involve the influence of the synergistic coordination of more than five metals and polyanions on the performance of lithium-rich manganese materials, but also does not involve a double coating layer structure. In addition, although polyanion co-doped lithium-manganese-rich cathode materials and high-entropy lithium-manganese-rich cathode materials are very common, there is no prior art that discloses that polyanions can be doped inside the high-entropy lithium-manganese-rich lattice while also in-situ covering the surface of the material to form a double coating layer. Summary of the invention
[0005] The technical problem solved by the present invention is to overcome the defects of the lithium-rich manganese positive electrode materials in the prior art, such as low initial coulomb efficiency, poor rate capacity, and severe voltage decay in practical applications, and provide a double-coated lithium-rich manganese-based material and a preparation method, application, and battery. The double-coated lithium-rich manganese-based material prepared by the present invention has fine particles, uniform doping elements, and complete coating; the preparation method is simple and the cost is low; when preparing lithium-ion batteries, it has high initial capacity, excellent cycle stability, and excellent electrochemical performance at high rates.
[0006] The present invention provides a double-coated lithium-rich manganese-based material, the chemical formula of which is Li x Mn y Ni z M 2-x-y-z S w O 2-w ·A a B b , part of the anion S enters the lattice, and the other part of the anion S forms the first coating layer in the form of metal salts and covers the surface of the material, while A a B bThe second coating layer is formed in situ on the surface of the first coating layer. The present invention prepares the sodium salt precursor by the sol-gel method, and ion-exchanges the phase, doping the polyanion while preparing the lithium-rich manganese material, and generating A in situ during the ion exchange process. a B b , which can effectively improve the electrochemical performance of lithium-rich manganese materials. The sol-gel-ion exchange method will assist the doping of large-radius metal ions and polyanions that are difficult to achieve with ordinary lithium battery positive electrode materials, allowing the doped ions to evenly enter the lattice structure and generate A in situ a B b Coating layer, to prepare the polyanion co-doped double-coated lithium-rich manganese material, which has never been realized before, with fine particles and uniform doping elements. From the perspective of mechanism, part of the polyanions enter the lattice to alleviate the structural damage during the cycle, and part of the polyanions are in situ coated on the particle surface to expand the lithium ion transmission channel and protect the electrolyte from damage to the material. The mixed arrangement of high entropy metal ions in the metal layer and the occupation of the lithium ion layer also inhibit the trend of lithium ions migrating to the TM layer during the cycle, effectively preventing voltage decay; while metal ions and anions with larger radius and difficult to enter the lattice will be in situ generated on the material surface in the form of metal salts during the ion exchange process, which plays a role in expanding the lithium ion channel, isolating the contact between the electrolyte and the material, alleviating the irreversible phase change, and stabilizing the layered structure.
[0007] The present invention solves the above technical problems through the following technical solutions:
[0008] The present invention provides a double-coated lithium-rich manganese-based material, the chemical formula of which is Li x Mn y Ni z M 2-x-y-z S w O 2-w ·(0.2-2)mol%A a B b , wherein M includes any three or more of Mg, Al and transition metals, S includes PO4 and / or BO3, A includes one or more of Ca, Sr, Ba and lanthanide metals, and B includes one or more of SO4, PO4, SiO3, SiF6, BF4 and SiO4; 1<x≤1.5, 0.1<y≤0.6, 0.02<z≤0.3, 0<w≤0.5, 1≤a≤3, 1≤b≤4.
[0009] In the present invention, the mol% generally refers to A a B b With Li x Mn y Ni z M 2-x-y-z S w O2-w The mole percentage of .
[0010] In the present invention, preferably, the internal Li x Mn y Ni z M 2-x-y-z S w O 2-w In the present invention, part of the polyanion S is located inside the crystal lattice of the material, and part of the polyanion S forms a coating layer in the form of metal salt that covers the surface of the material.
[0011] In the present invention, preferably, in the double-coated lithium-rich manganese-based material, A a B b Coated with Li x Mn y Ni z M 2-x-y- z S w O 2-w surface.
[0012] In the present invention, the double-coated lithium-rich manganese-based material preferably has a double coating layer, part of the polyanion S is located inside the material lattice, and part of the polyanion S forms a first coating layer in the form of a metal salt and is coated on the surface of the material, and A a B b Then, a second coating layer is in-situ generated on the surface of the first coating layer to form.
[0013] In the present invention, the transition metal preferably includes one or more of Sc, Ti, V, Cr, Fe, Co, Cu, Zn, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd and Cd.
[0014] In the present invention, the lanthanide metal preferably includes one or more of La, Ce, Pr, Nd, Pm and Sm.
[0015] In the present invention, in the chemical formula, preferably, 1<x≤1.3, for example, 1.16 or 1.18.
[0016] In the present invention, in the chemical formula, preferably, 0.4<y≤0.6, for example, 0.54.
[0017] In the present invention, in the chemical formula, preferably, 0.03<z≤0.2, for example, 0.06, 0.09 or 0.11.
[0018] In the present invention, in the chemical formula, preferably, 0<w≤0.1, for example, 0.04, 0.06 or 0.08.
[0019] In the present invention, in the chemical formula, A a Bb The molar ratio is preferably (0.2-1) mol %, such as 0.5 mol %, 0.8 mol % or 1 mol %.
[0020] In a specific embodiment, the M is Mg, Co, Al and Cu.
[0021] In a specific embodiment, the S is PO4 and BO3.
[0022] In a specific embodiment, the A a B b It is BaSO4 or Ba3(PO4)2.
[0023] In a specific embodiment, the chemical formula is:
[0024] Li 1.18 Mg 0.02 Mn 0.54 Ni 0.11 Co 0.11 Al 0.02 Cu 0.02 (PO4) 0.02 (BO3) 0.02 O 1.96 0.5mol%BaSO4, Li 1.18 Mg 0.02 Mn 0.54 Ni 0.11 Co 0.09 Al 0.04 Cu 0.02 (PO4) 0.04 (BO3) 0.02 O 1.94 0.5mol%BaSO4, Li 1.16 Mg 0.04 Mn 0.54 Ni 0.09 Co 0.09 Al 0.04 Cu 0.04 (PO4) 0.02 (BO3) 0.04 O 1.94 1mol%BaSO4, Li 1.18 Mg 0.02 Mn 0.54 Ni 0.06 Co 0.09 Al 0.04 Cu 0.07 (PO4) 0.04 (BO3) 0.04 O 1.92 1mol%BaSO4, Li 1.18 Mg0.02 Mn 0.54 Ni 0.06 Co 0.06 Al 0.07 Cu 0.07 (PO4) 0.04 (BO3) 0.04 O 1.92 ·1 mol% BaSO4.
[0025] In the present invention, the double-coated lithium-rich manganese-based material has a first-cycle discharge capacity of 270-320 mAh g at 0.1C and in a voltage range of 2-4.8V. –1 , preferably 280-310 mAh g –1 .
[0026] In the present invention, the first cycle discharge capacity of the double-coated lithium-rich manganese-based material at 0.1C and in the voltage range of 1.5-4.8V can be 340-400mAh g –1 , preferably 360-380mAh g –1 .
[0027] In the present invention, the double-coated lithium-rich manganese-based material has a first-cycle discharge capacity of 400-480 mAh g at 0.1C and in a voltage range of 1-4.8V. –1 , preferably 420-440mAh g –1 .
[0028] In the present invention, the capacity retention rate of the double-coated lithium-rich manganese-based material after 200 cycles at a current of 1C is preferably greater than 70%, and more preferably greater than 90%.
[0029] The present invention also provides a method for preparing the double-coated lithium-rich manganese-based material, which comprises the following steps:
[0030] (1) heating a mixed solution containing a lithium source, a sodium source, a manganese source, a nickel source, an M source, an S source, a solvent and a complexing agent to form a gel, and then calcining the gel to obtain a sodium salt precursor;
[0031] (2) calcining and washing the mixture of the sodium salt precursor, lithium salt, source A and source B to obtain the double-coated lithium-rich manganese-based material.
[0032] In step (1), the chemical formula of the sodium salt precursor is generally Na x1 Li x-x1 Mn y Ni z M 2-x-y-z S w O 2-wThe meaning and range of each letter are the same as mentioned above, wherein 0.9<x1<1.1, preferably 0.95<x1<1.05, for example 1.0.
[0033] In step (1), the amount of the lithium source, sodium source, manganese source, nickel source, M source, and S source can be added in a stoichiometric ratio according to the chemical formula of the sodium salt precursor. According to the conventional art, the amount of the lithium source is generally 1-1.1 times the theoretical addition amount, for example 1.05 times.
[0034] In step (1), the lithium source is generally a lithium salt soluble in the solvent, preferably including one or more of lithium chloride, lithium bromide, lithium iodide, lithium nitrate, lithium acetate, lithium carbonate, lithium phosphate and lithium borate, such as lithium acetate.
[0035] In step (1), the sodium source is generally a sodium salt soluble in the solvent, preferably including one or more of sodium acetate, sodium nitrate and sodium chloride.
[0036] In step (1), the manganese source is generally a manganese salt soluble in the solvent, preferably including one or more of manganese acetate, manganese nitrate and manganese chloride.
[0037] In step (1), the nickel source is generally a nickel salt soluble in the solvent, preferably including one or more of nickel acetate, nickel nitrate and nickel chloride.
[0038] In step (1), the M source may be one or more of acetate, nitrate and chloride of the corresponding metal.
[0039] In a specific embodiment, the M source is magnesium acetate, cobalt acetate tetrahydrate, aluminum acetate and copper acetate monohydrate.
[0040] In step (1), the S source may be a salt or acid containing a corresponding anion, such as one or more of lithium phosphate, lithium borate, ammonium phosphate and boric acid.
[0041] In a specific embodiment, the S source is ammonium phosphate and boric acid.
[0042] In step (1), the solvent may be one or more of deionized water, isopropanol, ethylene glycol, anhydrous ethanol, dimethylformamide and acetone.
[0043] In step (1), the sum of the mass concentrations of the lithium source, the sodium source, the manganese source, the nickel source, the M source and the S source may be conventional in the art, generally (0.1-0.5) g / mL, preferably (0.2-0.4) g / mL, for example 0.29 g / mL, 0.3 g / mL or 0.4 g / mL.
[0044] In step (1), the complexing agent may be one or more of citric acid, maleic acid, glycine, ethyl acetate, ethanolamine and ethylenediaminetetraacetic acid.
[0045] In step (1), the amount of the complexing agent is generally 0.5-2 times the sum of the molar amounts of all metal ions in the manganese source, the nickel source and the M source, preferably 1-2 times, for example 1 time or 1.5 times.
[0046] In step (1), the method for preparing the mixed solution is preferably: adding the lithium source, the sodium source, the manganese source, the nickel source, the M source and the S source to the solvent, then adding the complexing agent, and stirring at room temperature until completely dissolved.
[0047] In step (1), the heating temperature may be 60-150°C, preferably 70-100°C, such as 80°C. The heating time may be 6-24h, preferably 10-18h, such as 14h. The heating is preferably carried out under stirring. The stirring speed may be 100-500rpm, preferably 200-300rpm, such as 250rpm.
[0048] In step (1), the gel is generally dried before calcination. The drying method may be conventional in the art, such as oven drying. The drying temperature may be 100-150°C, such as 120°C.
[0049] In step (1), the calcination is generally carried out in a muffle furnace. The calcination temperature may be 700-1000°C, such as 900°C or 1000°C. The calcination time may be 8-15h, such as 12h. The rate of heating to the calcination temperature may be 1-10°C / min. The cooling rate after calcination may be 1-10°C / min.
[0050] In step (2), the lithium salt may include one or more of lithium chloride, lithium bromide, lithium iodide, lithium nitrate, lithium acetate, lithium carbonate, lithium phosphate and lithium borate.
[0051] In step (2), A and B have the same meanings as in the aforementioned chemical formula and are not described in detail here.
[0052] In step (2), the A source may be a salt containing metal A ions, such as acetate and / or nitrate.
[0053] In step (2), the B source may be a salt or acid containing a corresponding anion, such as one or more of ammonium phosphate, ammonium sulfate, lithium phosphate, lithium sulfate, lithium silicate, lithium borate, lithium hexafluorosilicate, lithium tetrafluoroborate, lithium metasilicate and boric acid.
[0054] In a specific embodiment, the A source is barium acetate and the B source is ammonium sulfate.
[0055] In step (2), the molar ratio of the sodium salt precursor to the lithium salt may be 1:(1.5-3), for example 1:2 or 1:2.5.
[0056] In step (2), the molar ratio of the A source to the sodium salt precursor may be 0.2%-2%, preferably 0.2%-1%, such as 0.5%, 0.8% or 1%.
[0057] In step (2), the amount of A ions in the A source and the amount of B ions in the B source are generally added in a stoichiometric ratio according to the chemical formula.
[0058] In step (2), the mixture is generally ground before calcination.
[0059] In step (2), the calcination is generally carried out in a muffle furnace. The calcination temperature is generally higher than the melting point of the lithium salt, preferably 10° C. above the melting point of the lithium salt and below 200° C. The calcination time can be 3-10 hours, preferably 4-6 hours, for example 5 hours.
[0060] When the lithium salt is lithium chloride, the calcination temperature may be 620-800°C, such as 650°C or 700°C.
[0061] In step (2), the solvent used for washing can be deionized water and / or a polar organic solvent. The polar organic solvent can be one or more of methanol, ethanol, propanol, ethylene glycol, glycerol, ethylenediamine, acetonitrile, DMF and DMSO. The washing method can be suction filtration. In order to better remove impurity ions, the calcined product can also be immersed in the solvent for a period of time and then suction filtered.
[0062] In step (2), according to the common practice in the art, the washing is generally followed by drying. The drying method may be conventional in the art, such as oven drying. The drying temperature may be 60-150° C., preferably 70-100° C., such as 80° C. The drying time may be 2-12 h, preferably 6-10 h, such as 8 h.
[0063] The present invention also provides a double-coated lithium-rich manganese-based material prepared by the preparation method as described above.
[0064] The present invention also provides an application of the double-coated lithium-rich manganese-based material as described above in a lithium-ion battery.
[0065] The present invention also provides a lithium-ion battery, which includes the double-coated lithium-rich manganese-based material as described above.
[0066] In the present invention, the double-coated lithium-rich manganese-based material is preferably used as a positive electrode material in a lithium-ion battery.
[0067] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0068] The reagents and raw materials used in the present invention are commercially available.
[0069] The positive and progressive effects of the present invention are:
[0070] The double-coated lithium-rich manganese-based material prepared by the present invention has fine particles and uniform doping elements; the preparation method is simple and the cost is low; when preparing lithium-ion batteries, it has high initial capacity, excellent cycle stability and excellent electrochemical performance at high rates. BRIEF DESCRIPTION OF THE DRAWINGS
[0071] Figure 1 This is a SEM image of the double-coated lithium-rich manganese-based material prepared in Example 1;
[0072] Figure 2 This is the XRD pattern of the double-coated lithium-rich manganese-based material prepared in Example 1;
[0073] Figure 3 HRTEM images of lithium-rich manganese-based materials prepared in Example 1 and Comparative Examples 1-3;
[0074] Figure 4 This is a 2-4.8V first cycle capacity performance diagram of the double-coated lithium-rich manganese-based material prepared in Example 1;
[0075] Figure 5 This is a first cycle capacity performance diagram of 1.5-4.8V of the double-coated lithium-rich manganese-based material prepared in Example 1;
[0076] Figure 6 This is a first cycle capacity performance diagram of 1.0-4.8V of the double-coated lithium-rich manganese-based material prepared in Example 1;
[0077] Figure 7 This is a cycle performance diagram of the double-coated lithium-rich manganese-based material prepared in Example 1 at 1C (2-4.8V);
[0078] Figure 8 This is a cycle performance diagram of the double-coated lithium-rich manganese-based material prepared in Example 1 at 0.1C (2-4.8V);
[0079] Fig. 9 This is the first cycle capacity performance diagram of the double-coated lithium-rich manganese-based material prepared in Example 2-4 at 0.1C (2-4.8V);
[0080] Fig.10The cycle performance diagram of the double-coated lithium-rich manganese-based material prepared in Example 2-4 at 1C (2-4.8V);
[0081] Fig.11 The first cycle capacity performance diagram of the lithium-rich manganese material prepared in Comparative Examples 1-3 at 0.1C (2-4.8V);
[0082] Fig.12 This is a cycle performance diagram of the lithium-rich manganese material prepared in Comparative Examples 1-3 at 1C (2-4.8V). DETAILED DESCRIPTION
[0083] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0084] Example 1
[0085] Double-coated lithium-rich manganese-based material Li 1.18 Mg 0.02 Mn 0.54 Ni 0.11 Co 0.11 Al 0.02 Cu 0.02 (PO4) 0.02 (BO3) 0.02 O 1.96 0.5mol%BaSO4 preparation:
[0086] S1, weigh 50mmol sodium acetate, 9.45mmol lithium acetate, 1mmol magnesium acetate, 27mmol manganese acetate, 5.5mmol nickel acetate tetrahydrate, 5.5mmol cobalt acetate tetrahydrate, 1mmol aluminum acetate, 1mmol copper acetate monohydrate, 1mmol ammonium phosphate, 1mmol boric acid, dissolve in 50mL water, add 61.5mmol citric acid monohydrate, and stir at room temperature to completely dissolve;
[0087] S2, stirring the solution at 80°C and 250 rpm for 14 h to make it into a gel; drying it at 120°C for 12 h to make a dry gel; placing the dry gel in a muffle furnace and heating it to 900°C at a heating rate of 5°C / min for 12 h, then cooling it to room temperature at a cooling rate of 5°C / min to obtain the sodium salt precursor NaLi 0.18 Mg 0.02 Mn 0.54 Ni 0.11 Co 0.11 Al 0.02 Cu 0.02 (PO4) 0.02 (BO3)0.02 O 1.96 ;
[0088] S3, weigh 5 mmol of sodium salt precursor, 12.5 mmol of lithium chloride, 0.025 mmol of barium acetate, and 0.025 mmol of ammonium sulfate, grind and mix them, transfer them to a muffle furnace, and calcine them at 650°C for 5 h;
[0089] S4, filtering the calcined product with ethanol and drying it at a temperature of 80° C. for 8 h to obtain a double-coated lithium-rich manganese-based material.
[0090] Example 2
[0091] Double-coated lithium-rich manganese-based material Li 1.18 Mg 0.02 Mn 0.54 Ni 0.11 Co 0.09 Al 0.04 Cu 0.02 (PO4) 0.04 (BO3) 0.02 O 1.94 0.5mol%BaSO4 preparation:
[0092] S1, weigh 50mmol sodium acetate, 9.45mmol lithium acetate, 1mmol magnesium acetate, 27mmol manganese acetate, 5.5mmol nickel acetate tetrahydrate, 4.5mmol cobalt acetate tetrahydrate, 2mmol aluminum acetate, 1mmol copper acetate monohydrate, 2mmol ammonium phosphate, 1mmol boric acid, dissolve in 50mL water, add 61.5mmol citric acid monohydrate, and stir at room temperature to completely dissolve;
[0093] S2, stirring the solution at 80°C and 250 rpm for 14 h to make it into a gel; drying it at 120°C for 12 h to make a dry gel; placing the dry gel in a muffle furnace and heating it to 900°C at a heating rate of 5°C / min for 12 h, then cooling it to room temperature at a cooling rate of 5°C / min to obtain the sodium salt precursor NaLi 0.18 Mg 0.02 Mn 0.54 Ni 0.11 Co 0.09 Al 0.04 Cu 0.02 (PO4) 0.04 (BO3) 0.02 O 1.94 ;
[0094] S3, weigh 5 mmol of sodium salt precursor, 12.5 mmol of lithium chloride, 0.025 mmol of barium acetate, and 0.025 mmol of ammonium sulfate, grind and mix them, transfer them to a muffle furnace, and calcine them at 650°C for 5 h;
[0095] S4, filtering and drying the calcined product with ethanol, the drying temperature is 80° C., and the drying time is 8 h, to obtain a double-coated lithium-rich manganese-based material.
[0096] Example 3
[0097] Double-coated lithium-rich manganese-based material Li 1.16 Mg 0.04 Mn 0.54 Ni 0.09 Co 0.09 Al 0.04 Cu 0.04 (PO4) 0.02 (BO3) 0.04 O 1.94 1mol% BaSO4 preparation:
[0098] S1, weigh 50mmol sodium acetate, 8.4mmol lithium acetate, 2mmol magnesium acetate, 27mmol manganese acetate, 4.5mmol nickel acetate tetrahydrate, 4.5mmol cobalt acetate tetrahydrate, 2mmol aluminum acetate, 2mmol copper acetate monohydrate, 1mmol ammonium phosphate, 2mmol boric acid, dissolve in 50mL water, add 63mmol citric acid monohydrate, and stir at room temperature to completely dissolve;
[0099] S2, stirring the solution at 80°C and 250 rpm for 14 h to make it into a gel; drying it at 120°C for 12 h to make a dry gel; placing the dry gel in a muffle furnace and heating it to 900°C at a heating rate of 5°C / min for 12 h, then cooling it to room temperature at a cooling rate of 5°C / min to obtain the sodium salt precursor NaLi 0.16 Mg 0.04 Mn 0.54 Ni 0.09 Co 0.09 Al 0.04 Cu 0.04 (PO4) 0.02 (BO3) 0.04 O 1.94 ;
[0100] S3, weigh 5 mmol of sodium salt precursor, 12.5 mmol of lithium chloride, 0.05 mmol of barium acetate, and 0.05 mmol of ammonium sulfate, grind and mix them, transfer them to a muffle furnace, and calcine them at 650°C for 5 h;
[0101] S4, filtering and drying the calcined product with ethanol, the drying temperature is 80° C., and the drying time is 8 h, to obtain a double-coated lithium-rich manganese-based material.
[0102] Example 4
[0103] Double-coated lithium-rich manganese-based material Li 1.18 Mg 0.02 Mn 0.54 Ni 0.06 Co 0.09 Al 0.04 Cu 0.07 (PO4) 0.04 (BO3) 0.04 O 1.92 1mol% BaSO4 preparation:
[0104] S1, weigh 50mmol sodium acetate, 9.45mmol lithium acetate, 1mmol magnesium acetate, 27mmol manganese acetate, 3mmol nickel acetate tetrahydrate, 4.5mmol cobalt acetate tetrahydrate, 2mmol aluminum acetate, 3.5mmol copper acetate monohydrate, 2mmol ammonium phosphate, 2mmol boric acid, dissolve in 50mL water, add 61.5mmol citric acid monohydrate, and stir at room temperature to completely dissolve;
[0105] S2, stirring the solution at 80°C and 250 rpm for 14 h to make it into a gel; drying it at 120°C for 12 h to make a dry gel; placing the dry gel in a muffle furnace and heating it to 900°C at a heating rate of 5°C / min for 12 h, then cooling it to room temperature at a cooling rate of 5°C / min to obtain a sodium salt precursor, NaLi 0.18 Mg 0.02 Mn 0.54 Ni 0.06 Co 0.09 Al 0.04 Cu 0.07 (PO4) 0.04 (BO3) 0.04 O 1.92 ;
[0106] S3, weigh 5 mmol of sodium salt precursor, 12.5 mmol of lithium chloride, 0.05 mmol of barium acetate, and 0.05 mmol of ammonium sulfate, grind and mix them, transfer them to a muffle furnace, and calcine them at 650°C for 5 h;
[0107] S4, filtering and drying the calcined product with ethanol, the drying temperature is 80° C., and the drying time is 8 h, to obtain a double-coated lithium-rich manganese-based material.
[0108] Example 5
[0109] Double-coated lithium-rich manganese-based material Li1.18 Mg 0.02 Mn 0.54 Ni 0.06 Co 0.06 Al 0.07 Cu 0.07 (PO4) 0.04 (BO3) 0.04 O 1.92 1mol% BaSO4 preparation:
[0110] S1, weigh 50mmol sodium acetate, 9.45mmol lithium acetate, 1mmol magnesium acetate, 27mmol manganese acetate, 3mmol nickel acetate tetrahydrate, 3mmol cobalt acetate tetrahydrate, 3.5mmol aluminum acetate, 3.5mmol copper acetate monohydrate, 2mmol ammonium phosphate, 2mmol boric acid, dissolve in 50mL water, add 61.5mmol citric acid monohydrate, and stir at room temperature to completely dissolve;
[0111] S2, stirring the solution at 80°C and 250 rpm for 14 h to make it into a gel; drying it at 120°C for 12 h to make a dry gel; placing the dry gel in a muffle furnace and heating it to 900°C at a heating rate of 5°C / min for 12 h, then cooling it to room temperature at a cooling rate of 5°C / min to obtain the sodium salt precursor NaLi 0.18 Mg 0.02 Mn 0.54 Ni 0.06 Co 0.06 Al 0.07 Cu 0.07 (PO4) 0.04 (BO3) 0.04 O 1.92 ;
[0112] S3, weigh 5 mmol of sodium salt precursor, 12.5 mmol of lithium chloride, 0.05 mmol of barium acetate, and 0.05 mmol of ammonium sulfate, grind and mix them, transfer them to a muffle furnace, and calcine them at 650°C for 5 h;
[0113] S4, filtering and drying the calcined product with ethanol, the drying temperature is 80° C., and the drying time is 8 h, to obtain a double-coated lithium-rich manganese-based material.
[0114] Comparative Example 1
[0115] Lithium-rich manganese-based materials 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2 preparation:
[0116] S1, weigh 50mmol sodium acetate, 10.5mmol lithium acetate, 27mmol manganese acetate, 6.5mmol nickel acetate tetrahydrate, 6.5mmol cobalt acetate tetrahydrate, dissolve in 50ml water, add 60mmol citric acid monohydrate, and stir at room temperature to completely dissolve;
[0117] S2, stirring the solution at 80°C and 250 rpm for 14 h to make it into a gel; drying it at 120°C for 12 h to make a dry gel; placing the dry gel in a muffle furnace and heating it to 900°C at a heating rate of 5°C / min for 12 h, then cooling it to room temperature at a cooling rate of 5°C / min to obtain the sodium salt precursor NaLi 0.2 Mn 0.54 Ni 0.13 Co 0.13 O2;
[0118] S3, weigh 5 mmol of sodium salt precursor and 12.5 mmol of lithium chloride, grind and mix them, transfer them to a muffle furnace and calcine them at 650 °C for 5 h;
[0119] S4, the calcined product is filtered and dried with ethanol at a drying temperature of 80° C. for 8 h to obtain the final product.
[0120] Comparative Example 2
[0121] Lithium-rich manganese-based materials 1.18 Mg 0.02 Mn 0.54 Ni 0.11 Co 0.11 Al 0.02 Cu 0.02 (PO4) 0.02 (BO3) 0.02 O 1.96 preparation:
[0122] S1, weigh 50mmol sodium acetate, 9.45mmol lithium acetate, 1mmol magnesium acetate, 27mmol manganese acetate, 5.5mmol nickel acetate tetrahydrate, 5.5mmol cobalt acetate tetrahydrate, 1mmol aluminum acetate, 1mmol copper acetate monohydrate, 1mmol ammonium phosphate, 1mmol boric acid, dissolve in 50mL water, add 61.5mmol citric acid monohydrate, and stir at room temperature to completely dissolve;
[0123] S2, stirring the solution at 80°C and 250 rpm for 14 h to make it into a gel; drying it at 120°C for 12 h to make a dry gel; placing the dry gel in a muffle furnace and heating it to 900°C at a heating rate of 5°C / min for 12 h, then cooling it to room temperature at a cooling rate of 5°C / min to obtain the sodium salt precursor NaLi 0.18Mg 0.02 Mn 0.54 Ni 0.11 Co 0.11 Al 0.02 Cu 0.02 (PO4) 0.02 (BO3) 0.02 O 1.96 ;
[0124] S3, weigh 5 mmol of sodium salt precursor and 12.5 mmol of lithium chloride, grind and mix them, transfer them to a muffle furnace and calcine them at 650 °C for 5 h;
[0125] S4, the calcined product is filtered and dried with ethanol, the drying temperature is 80°C, and the drying time is 8h to obtain the final product.
[0126] Comparative Example 3
[0127] Lithium-rich manganese-based materials 1.18 Mg 0.02 Mn 0.54 Ni 0.11 Co 0.11 Al 0.02 Cu 0.02 O2 preparation:
[0128] S1, weigh 50mmol sodium acetate, 9.45mmol lithium acetate, 1mmol magnesium acetate, 27mmol manganese acetate, 5.5mmol nickel acetate tetrahydrate, 5.5mmol cobalt acetate tetrahydrate, 1mmol aluminum acetate, 1mmol copper acetate monohydrate, dissolve in 50ml water, add 61.5mmol citric acid monohydrate, and stir at room temperature to completely dissolve;
[0129] S2, stirring the solution at 80°C and 250 rpm for 14 h to make it into a gel; drying it at 120°C for 12 h to make a dry gel; placing the dry gel in a muffle furnace and heating it to 900°C at a heating rate of 5°C / min for 12 h, then cooling it to room temperature at a cooling rate of 5°C / min to obtain the sodium salt precursor NaLi 0.18 Mg 0.02 Mn 0.54 Ni 0.11 Co 0.11 Al 0.02 Cu 0.0 2O2;
[0130] S3, weigh 5 mmol of sodium salt precursor and 12.5 mmol of lithium chloride, grind and mix them, transfer them to a muffle furnace and calcine them at 650 °C for 5 h;
[0131] S4, the calcined product is filtered and dried with ethanol, the drying temperature is 80°C, and the drying time is 8h to obtain the final product.
[0132] Comparative Example 4
[0133] Lithium-rich manganese-based materials 1.2 Mn 0.54 Ni 0.13 Co 0.13 (PO4) 0.02 (BO3) 0.02 O 1.96 preparation:
[0134] S1, weigh 50mmol sodium acetate, 10.5mmol lithium acetate, 27mmol manganese acetate, 6.5mmol nickel acetate tetrahydrate, 6.5mmol cobalt acetate tetrahydrate, 1mmol ammonium phosphate, 1mmol boric acid, dissolve in 50ml water, add 60mmol citric acid monohydrate, and stir at room temperature to completely dissolve;
[0135] S2, stirring the solution at 80°C and 250 rpm for 14 h to make it into a gel; drying it at 120°C for 12 h to make a dry gel; placing the dry gel in a muffle furnace and heating it to 900°C at a heating rate of 5°C / min for 12 h, then cooling it to room temperature at a cooling rate of 5°C / min to obtain the sodium salt precursor NaLi 0.2 Mn 0.54 Ni 0.13 Co 0.13 (PO4) 0.02 (BO3) 0.02 O 1.96 ;
[0136] S3, weigh 5 mmol of sodium salt precursor and 12.5 mmol of lithium chloride, grind and mix them, transfer them to a muffle furnace and calcine them at 650 °C for 5 h;
[0137] S4, the calcined product is filtered and dried with ethanol, the drying temperature is 80°C, and the drying time is 8h to obtain the final product.
[0138] Effect Example
[0139] (1) SEM, XRD and element content characterization
[0140] Figure 1 This is the SEM of the double-coated lithium-rich manganese-based material in Example 1. It can be seen from the figure that the sample particles are uniform in size and are nano-sized particles. Small-sized particles are conducive to the diffusion of lithium ions during the charge and discharge process, which helps to improve the electrochemical performance.
[0141] Figure 2This is the XRD of the double-coated lithium-rich manganese-based material in Example 1. It can be seen from the figure that the sample is a mixed phase of standard LiMO2 phase and Li2MnO3 phase, which is consistent with the XRD peak value of lithium-rich manganese material and has no unnecessary peaks.
[0142] from Figure 3 It can be seen that the barium sulfate-coated phosphate-borate co-doped lithium-rich manganese-based high-entropy positive electrode material in Example 1 has an obvious double-coating structure, in which the inner layer is a phosphate and borate amorphous coating, and the outer layer is a barium sulfate coating, and its lattice spacing conforms to the (001) crystal plane spacing of barium sulfate crystals, and they are all formed in situ. Compared with Comparative Example 1, Comparative Example 2 and Comparative Example 3 both have larger crystal plane spacings, indicating that the doping of metal ions and polyanions can expand the crystal plane spacing, among which the increase in the crystal plane spacing of Comparative Example 2 is greater than that of Comparative Example 3, indicating that the polyanion enters the lattice. At the same time, it can be seen that the surface of Comparative Example 2 has an obvious amorphous coating layer, which is formed in situ on the surface by the polyanion.
[0143] The phosphate-borate co-doped high entropy lithium-rich manganese-based cathode material Li prepared in Comparative Example 2 was prepared by ICP. 1.18 Mg 0.02 Mn 0.54 Ni 0.11 Co 0.11 Al 0.02 Cu 0.02 (PO4) 0.02 (BO3) 0.02 O 1.96 An analysis was carried out, and the elemental analysis results are shown in Table 1. From Table 1, it can be seen that the atomic ratio obtained by ICP test is consistent with the raw material ratio put into the experiment and the designed chemical formula.
[0144] Table 1
[0145] element Mass concentration (mg / L) Atomic Ratio Li concentration 6.94 0.580 Mn concentration 53.94 0.260 Ni concentration 58.69 0.055 Mg concentration 24.31 0.010 Co concentration 58.93 0.055 Al concentration 26.98 0.010 Cu concentration 63.59 0.010 P concentration 30.74 0.010 B concentration 10.81 0.010
[0146] (2) Electrochemical performance test
[0147] The electrochemical performance of the final products prepared in the above embodiments and comparative examples was evaluated using CR2032 button batteries.
[0148] The final product materials prepared in Examples 1-5 and Comparative Examples 1-4, SuperP and polyvinylidene fluoride (PVDF) were uniformly mixed at a mass ratio of 8:1:1 to prepare an electrode slurry in NMP solvent. The electrode slurry was then evenly coated on aluminum foil using a coating machine and dried overnight in a vacuum environment at 120°C. Finally, a cathode sheet with a diameter of 13 mm was punched on a tablet press, and the loading amount was about 2-3 mg cm -2. The prepared electrode was used as the positive electrode, pure lithium as the counter electrode, Celgard2500 as the separator, and the organic electrolyte was 1.0M LiPF6in EC:DMC:EMC=1:1:1Vol%+5wt%FEC (i.e., the volume ratio of EC:DMC:EMC was 1:1:1, and the percentage of FEC in the total mass of the electrolyte was 5%) to assemble a CR2032 coin-type half-cell. The obtained battery was subjected to charge and discharge tests on an electrochemical workstation, 1C=250mAh g -1 The test results are shown in Figure 4-Figure 12 and Table 2:
[0149] Table 2
[0150] sample Voltage range First cycle discharge specific capacity 200 cycles capacity retention rate Example 1 2-4.8V <![CDATA[308mAhg -1 ]]> 96.8% Example 2 2-4.8V <![CDATA[281mAhg -1 ]]> 71.6% Example 3 2-4.8V <![CDATA[291mAhg -1 ]]> 94.3% Example 4 2-4.8V <![CDATA[289mAhg -1 ]]> 85.5% Example 5 2-4.8V <![CDATA[287mAhg -1 ]]> 73.5% Comparative Example 1 2-4.8V <![CDATA[237mAhg -1 ]]> 76.9% Comparative Example 2 2-4.8V <![CDATA[265mAhg -1 ]]> 66.7% Comparative Example 3 2-4.8V <![CDATA[234mAhg -1 ]]> 82.8% Comparative Example 4 2-4.8V <![CDATA[253mAhg -1 ]]> 78.4%
[0151] According to the data of Examples 1-5, the prepared double-coated lithium-rich manganese-based material not only has a better capacity retention rate, but also has a higher first-cycle discharge specific capacity, and the first-cycle discharge specific capacity is even as high as 308 mAh g -1 .
[0152] According to Comparative Example 1, when the prepared lithium-rich manganese-based material contains less than five metal species other than lithium, has no anion doping, and does not contain a barium sulfate coating layer, the first cycle discharge capacity is only 237 mAh g -1 , much lower than the embodiment.
[0153] According to Comparative Examples 2-4, it can be seen that when the prepared lithium-rich manganese-based material does not contain a barium sulfate coating layer, or the prepared lithium-rich manganese-based material has neither anion doping nor a barium sulfate coating layer, or the prepared lithium-rich manganese-based material is doped with anions but the metal types are less than five and there is no barium sulfate coating layer, it still has a low first-cycle discharge specific capacity.
[0154] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.
Claims
1. A double-coated lithium-rich manganese-based material, characterized in that: Its chemical formula is Li x Mn y Ni z M 2-x-y-z S w O 2-w (0.2-2) mol% A a B b , wherein M includes any three or more of Mg, Al and transition metals, S includes PO4 and / or BO3, A includes one or more of Ca, Sr, Ba and lanthanide metals, and B includes one or more of SO4, PO4, SiO3, SiF6, BF4 and SiO4; 1<x≤1.5, 0.1<y≤0.6, 0.02<z≤0.3, 0<w≤0.5, 1≤a≤3, 1≤b≤4.
2. The double-coated lithium-rich manganese-based material according to claim 1, characterized in that: The positive electrode material meets one or more of the following conditions: (1) In the double-coated lithium-rich manganese-based material, A a B b Coated with Li x Mn y Ni z M 2-x-y-z S w O 2-w Surface (2) Li inside x Mn y Ni z M 2-x-y-z S w O 2-w In the process, part of the polyanion S is located inside the material lattice, and part of the polyanion S forms a coating layer in the form of metal salts that covers the surface of the material; (3) In the chemical formula, 1<x≤1.3, for example, 1.16 or 1.18; (4) In the chemical formula, 0.4<y≤0.6, for example, 0.54; (5) In the chemical formula, 0.03<z≤0.2, such as 0.06, 0.09 or 0.11; (6) In the chemical formula, 0<w≤0.1, for example, 0.04, 0.06 or 0.08; (7) In the chemical formula, A a B b The molar ratio is (0.2-1) mol%, such as 0.5 mol%, 0.8 mol% or 1 mol%; (8) The transition metal includes one or more of Sc, Ti, V, Cr, Fe, Co, Cu, Zn, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd and Cd; (9) The lanthanide metal includes one or more of La, Ce, Pr, Nd, Pm and Sm.
3. The double-coated lithium-rich manganese-based material according to claim 1, characterized in that: The M is Mg, Co, Al and Cu; And / or, the S is PO4 and BO3; and / or, the A a B b BaSO4 or Ba3(PO4)2; Or, the chemical formula is: Li 1.18 Mg 0.02 Mn 0.54 Ni 0.11 Co 0.11 Al 0.02 Cu 0.02 (PO4) 0.02 (BO3) 0.02 The 1.96 ·0.5mol%BaSO4、Li 1.18 Mg 0.02 Mn 0.54 Ni 0.11 Co 0.09 Al 0.04 Cu 0.02 (PO4) 0.04 (BO3) 0.02 The 1.94 ·0.5mol%BaSO4、Li 1.16 Mg 0.04 Mn 0.54 Ni 0.09 Co 0.09 Al 0.04 Cu 0.04 (PO4) 0.02 (BO3) 0.04 The 1.94 ·1mol%BaSO4、Li 1.18 Mg 0.02 Mn 0.54 Ni 0.06 Co 0.09 Al 0.04 Cu 0.07 (PO4) 0.04 (BO3) 0.04 The 1.92 ·1mol%BaSO4、or, Li 1.18 Mg 0.02 Mr 0.54 Ni 0.06 Co 0.06 Al 0.07 Cu 0.07 (PO4) 0.04 (BO3) 0.04 O 1.92 ·1mol%BaSO4。 4. A method for preparing a double-coated lithium-rich manganese-based material according to any one of claims 1 to 3, characterized in that: It includes the following steps: (1) heating a mixed solution containing a lithium source, a sodium source, a manganese source, a nickel source, an M source, an S source, a solvent and a complexing agent to form a gel, and then calcining the gel to obtain a sodium salt precursor; (2) calcining and washing the mixture of the sodium salt precursor, lithium salt, source A and source B to obtain the double-coated lithium-rich manganese-based material.
5. The method for preparing the double-coated lithium-rich manganese-based material according to claim 4, characterized in that: The preparation method meets one or more of the following conditions: (1) The chemical formula of the sodium salt precursor is Na x1 Li x-x1 Mn y Ni z M 2-x-y-z S w O 2-w , where 0.9<x1<1.1; (2) In step (1), the amount of the lithium source, sodium source, manganese source, nickel source, M source, and S source is added in a stoichiometric ratio according to the chemical formula of the sodium salt precursor; preferably, the amount of the lithium source is 1-1.1 times the theoretical amount added; (3) In step (1), the lithium source is a lithium salt soluble in the solvent, preferably including one or more of lithium chloride, lithium bromide, lithium iodide, lithium nitrate, lithium acetate, lithium carbonate, lithium phosphate and lithium borate; (4) In step (1), the sodium source is a sodium salt soluble in the solvent, preferably comprising one or more of sodium acetate, sodium nitrate and sodium chloride; (5) In step (1), the manganese source is a manganese salt soluble in the solvent, preferably including one or more of manganese acetate, manganese nitrate and manganese chloride; (6) In step (1), the nickel source is a nickel salt soluble in the solvent, preferably comprising one or more of nickel acetate, nickel nitrate and nickel chloride; (7) In step (1), the M source is one or more of acetate, nitrate and chloride of the corresponding metal; Preferably, the M source is magnesium acetate, cobalt acetate tetrahydrate, aluminum acetate and copper acetate monohydrate; (8) In step (1), the S source is a salt or acid containing a corresponding anion, such as one or more of lithium phosphate, lithium borate, ammonium phosphate and boric acid; Preferably, the S source is ammonium phosphate and boric acid.
6. The method for preparing the double-coated lithium-rich manganese-based material according to claim 4, characterized in that: The preparation method meets one or more of the following conditions: (1) In step (1), the solvent is one or more of deionized water, isopropanol, ethylene glycol, anhydrous ethanol, dimethylformamide and acetone; (2) In step (1), the sum of the mass concentrations of the lithium source, the sodium source, the manganese source, the nickel source, the M source and the S source is (0.1-0.5) g / mL, preferably (0.2-0.4) g / mL; (3) In step (1), the complexing agent is one or more of citric acid, maleic acid, glycine, ethyl acetate, ethanolamine and ethylenediaminetetraacetic acid; (4) In step (1), the amount of the complexing agent used is 0.5-2 times, preferably 1-2 times, the sum of the molar amounts of all metal ions in the manganese source, the nickel source and the M source.
7. The method for preparing the double-coated lithium-rich manganese-based material according to claim 4, characterized in that: The preparation method meets one or more of the following conditions: (1) In step (1), the mixed solution is prepared by adding the lithium source, the sodium source, the manganese source, the nickel source, the M source and the S source to the solvent, then adding the complexing agent, and stirring at room temperature until the mixture is completely dissolved; (2) In step (1), the heating temperature is 60-150° C., preferably 70-100° C.; (3) In step (1), the heating time is 6-24 hours, preferably 10-18 hours; (4) In step (1), the calcination temperature is 700-1000° C.; (5) In step (1), the calcination time is 8-15 hours.
8. The method for preparing the double-coated lithium-rich manganese-based material according to claim 4, characterized in that: The preparation method meets one or more of the following conditions: (1) In step (2), the lithium salt includes one or more of lithium chloride, lithium bromide, lithium iodide, lithium nitrate, lithium acetate, lithium carbonate, lithium phosphate and lithium borate; (2) In step (2), the molar ratio of the sodium salt precursor to the lithium salt is 1:(1.5-3); (3) In step (2), the A source is a salt containing metal A ions, such as acetate and / or nitrate; (4) In step (2), the B source is a salt or acid containing a corresponding anion, for example, one or more of ammonium phosphate, ammonium sulfate, lithium phosphate, lithium sulfate, lithium silicate, lithium borate, lithium hexafluorosilicate, lithium tetrafluoroborate, lithium metasilicate and boric acid; (5) In step (2), the molar ratio of the A source to the sodium salt precursor is 0.2%-2%, preferably 0.2%-1%, for example 0.5%, 0.8% or 1%; (6) In step (2), the calcination temperature is higher than the melting point of the lithium salt, preferably 10° C. or higher and 200° C. or lower than the melting point of the lithium salt; Preferably, when the lithium salt is lithium chloride, the calcination temperature is 620-800°C; (7) In step (2), the calcination time is 3-10 hours, preferably 4-6 hours.
9. Use of the double-coated lithium-rich manganese-based material according to any one of claims 1 to 3 in a lithium-ion battery.
10. A lithium ion battery, characterized in that: It comprises the double-coated lithium-rich manganese-based material as described in any one of claims 1 to 3.
Citation Information
Patent Citations
Layered lithium-rich manganese-based composite positive electrode material, preparation method and battery
CN114744186A
Preparation method of double-covering lithium-enriched manganese-based material using zirconium phosphate as outer covering and calcium fluoride as inner covering
CN106058203A
Preparation method of ternary positive electrode material of lithium ion power battery
CN112479270A
High-energy-efficiency lithium-manganese-rich positive electrode material as well as preparation method and application thereof
CN117954605A
Coated high nickel ternary material and preparation method therefor and use thereof
WO2022089204A1
